Evaluation of the possible influence of trailing and paradoxical effects on the clinical outcome of patients with candidemia. (January 2017) - Rueda, C.; Puig-Asensio, M.; Guinea, J.; Almirante, B.; Cuenca-Estrella, M.; Zaragoza, O.; ,
Abstract: Objective: Paradoxical growth (PG) and trailing effect (TE) are frequently observed during antifungal susceptibility testing (AFST). These two phenomena interfere with the determination of the minimal inhibitory concentration (MIC). The aim of this study was to assess the clinical impact of TE and PG. Methods: We analysed the frequency of TE and PG of 690 Candida isolates collected from a population-based study performed in Spain (CANDIPOP) and correlated the results with clinical outcome of the patients. Results: Around 70% (484/690) of the isolates exhibited TE to azoles. Candida tropicalis showed the highest presence of TE (39/53 isolates exhibited residual growth >25% of control). No TE was seen in most of the isolates from the psilosis complex. PG was mainly associated with echinocandins. In patients treated with fluconazole within the first 48 hours after blood sampling ( n  = 221), the presence of TE to azoles tended to be associated with lower 30-day mortality (odds ratio (OR) 0.55, 95% confidence interval (CI) 0.25–1.00) but not with clinical failure (OR 0.85, 95% CI 0.45–1.54). In the subgroup of 117 patients treated with echinocandins, the presence of PG was not associated with patient's response to antifungal treatment (OR for 30-day mortality 1.63, 95% CI 0.76–4.03; OR for clinical failure 1.17, 95% CI 0.53–2.70). Conclusions: TE or PG are widely expressed among Candida spp., although they do not seem to influence clinical outcome.